Association Between Nutritional Status and Anemia Among Adolescent Girls - Nur Ekawati; Nelly Nugrawati (PT. Nasyah Medika Care, 2024)
Background: Anemia remains one of the most common nutritional problems among adolescent girls, particularly in developing countries. Poor nutritional status during adolescence increases the risk of iron deficiency and anemia due to rapid growth, increased nutritional demands, and menstrual blood loss. Identifying the association between nutritional status and anemia is essential for developing effective prevention strategies. Research Objective: This study aims to determine the association between nutritional status and the incidence of anemia among adolescent girls in Makassar, Indonesia. Methods: This analytical observational study employed a cross-sectional design. A total of 41 adolescent girls aged 15–19 years were recruited using purposive sampling. Nutritional status was assessed using Body Mass Index-for-Age (BMI/A) based on the World Health Organization growth standards, while anemia status was determined by measuring hemoglobin concentration using a portable digital hemoglobin analyzer. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of p < 0.05. Results: Most respondents had normal nutritional status (56.1%), while 22.0% were underweight and 22.0% were overweight or obese. The prevalence of anemia was 41.5%. Bivariate analysis revealed a statistically significant association between nutritional status and anemia (p = 0.021). Adolescent girls with underweight nutritional status had a higher prevalence of anemia than those with normal nutritional status. Conclusion: Nutritional status was significantly associated with anemia among adolescent girls. Maintaining optimal nutritional status through balanced dietary intake, routine nutritional assessment, and regular anemia screening is essential to reduce anemia prevalence and improve adolescent health. These findings provide evidence for strengthening school-based nutrition education and anemia prevention programs.